Analisis Miskonsepsi Siswa SMA Pada Materi Elektrolit Dalam Pembelajaran Kimia - Nurul Khoiri Amalia (LPPM Universitas Negeri Jakarta, 2022)
This research is a descriptive study that aims to analyze and explain the misconceptions experienced by class X students on the electrolyte material. The research subjects were 29 students of class X IPA 2 at SMAN 1 Pangkalpinang. The data collection technique was carried out by distributing a written test in the form of a two-tier diagnostic test consisting of 30 multiple choice questions. The data that has been processed shows that there are misconceptions in class X students in the electrolyte material. The results of this study indicate that the misconceptions that occur in level 1 questions (recognizing material categories) are 38.79%; level 2 (understanding particle interactions) by 35.635%; and level 3 (explaining the problem quantitatively) of 55.662%.